Chronic Active Epstein-Barr Virus Infection With Systemic Vasculitis and Pulmonary Arterial Hypertension in a Child - Ba, Hongjun; Xu, Lingling; Peng, Huimin; Lin, Yuese; Li, Xuandi; Wang, Huishen; Qin, Youzhen (Frontiers in Pediatrics, 2019)
Introduction: A chronic active Epstein–Barr virus (EBV) infection (CAEBV), which is characterized by persistent ‘infectious mononucleosis-like’ symptoms, can lead to cardiovascular complications, including coronary artery aneurysms. No earlier reports highlight cases of chronic EB virus infection in conjunction with systemic vasculitis and pulmonary hypertension. Case presentation: Here, we present a case of CAEBV in a 9-year-old boy, associated with pulmonary arterial hypertension (PAH) and systemic vasculitis. Recurrent skin ulcers were a major early clinical manifestation in this case. The histopathological examination of a dermal biopsy sample from the lesions revealed vasculitis, and the in-situ hybridization test was positive for EBV-encoded small RNA. Results: The patient was administered immunosuppressants (prednisolone and cyclophosphamide) and drugs to control the pulmonary pressure (sildenafil and bosentan). This combination therapy decreased his systolic pulmonary arterial pressure to 40 mm Hg on echocardiography, and the N-terminal pro b-type natriuretic peptide level to 62.3 pg/ml. Conclusion: A CAEBV should be considered within the differential diagnosis while managing a pediatric patient with secondary PAH and systemic vasculitis. However, potential mechanisms need further study.